(untitled) (Asian Journal of Medical and Biological Research, 2024)
Medication errors represent a significant global issue, leading to numerous fatalities each year and adding complexity to healthcare systems. In Bangladesh, the prevalence of medication errors stands at 38%. This study aimed to identify the factors that influence medication errors among nurses at a tertiary-level hospital in the country. A descriptive cross-sectional study was conducted involving 114 registered nurses at Dhaka Medical College Hospital, utilizing a convenience sampling method. Data were gathered through face-to-face interviews using a structured questionnaire and analyzed using both descriptive and inferential statistics. The findings indicated that nurses in Bangladesh exhibited moderate to high susceptibility to medication errors in a tertiary-level setting. Key factors identified as contributing to these errors included inadequate staffing levels (4.41 ± 0.81), patients being off the ward for other care (4.39 ± 0.74), communication issues between nurses and physicians (4.36 ± 0.95), nurses being pulled between teams and other units (4.32 ± 0.77), and insufficient in-service training on new medications (4.23 ± 0.87). Moreover, nurses working ward (F=11.51, P=.001) and working experience (t=4.13, P=.041) had a significant relationship with factors influencing medication errors. The research found several variables that cause medication mistakes, including nurses’ service experience and working ward. This study’s results might help hospital administrators establish effective intervention methods and mitigate medication error risk variables to improve patient safety and care. Asian J. Med. Biol. Res. 2024, 10(4), 131-140